Fibrosarcoma of small bowel in a case of carcinoma ovary post cytoreductive surgery and hyperthermic intra peritoneal chemotherapy: a case report with review of literature - Pathak, Bhawani; Bhukkal, Bittu; Ray, Mukurdipo; Pramanik, Raja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Fibrosarcoma is a rare, malignant tumor of mesenchymal cell origin which derives from pathologically transformed spindle shaped fibroblasts with an excessively high division rate. There is no reported case of fibrosarcoma of the small intestine as a form of recurrence in carcinoma ovary post cytoreductive surgery and hyperthermic intra peritoneal chemotherapy (CRS and HIPEC). A 35-year-old female who is a known case of recurrent carcinoma ovary previously treated with cytoreductive surgery and HIPEC presented to emergency with features suggestive of intestinal obstruction. Upon exploration dense bowel adhesion and a segmental stricture with micro perforation without any leakage of intestinal content was discovered at 200 cm from DJ flexure. A diagnosis of fibrosarcoma was made on histopathological analysis. Recurrent carcinoma ovary patient treated with secondary CRS and HIPEC presenting with fibrosarcoma in small intestine is a rare entity and hardly any report in the literature. But appropriate diagnosis and management is the key for the successful outcome which we maintained in our case and managed successfully.